Analysis of the frequency deviation in off-grid power system of oil field. (November 2022) - Nesterenko, Gleb; Vakulenko, Vladimir; Zyryanov, Vyacheslav; Potapenko, Anton; Prankevich, Gleb; Aleksandrov, Makar
Abstract: The paper represents the results of field measurements in the off-grid power system of oil field including diesel power plant, which supplies drilling rig system BU-4500/270 EK-BM. The data has been processed using the instantaneous power theory by Hirofumi Akagi. The active power load diagram of diesel power plant and power system frequency schedule have been obtained for hole drilling technological process of drilling rig. Abrupt load changes during drilling lead to large frequency deviations, which do not allow using gas piston generators in power system of oil field without revision of number and rated power of generators or using electrical energy storage system.